Size frequency and length-weight relationships of spined anchovy, Stolephorus tri from the coastal waters of Besut, Terengganu, Malaysia - Zakaria, Mohd Hazmadi; Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz; Rahman, Md. Aminur; Al-Barwani, Said Mohammed Hilal (Academic Journals, 2011)
Study on length-weight relationships of anchovy, Stolephorus tri collected from Benting Lintang (Lat. 5°44'33.62 N and Long. 102°39'22.84 E), the coastal waters of Besut, Terengganu was carried out on June and July 2010. Stolephorus tri are important component of marine ecosystems and commercially significant marine food resources in Malaysia. The mean size length of Stolephorus tri was 63.53 mm with a range of 51.0-76.0 mm. The average weight of Stolephorus tri was 1.57 g. The relationship between total length and body weight of Stolephorus tri was Log W = 3.0384 Log TL-5.2923 (W = 0.00001 TL3.0384). It is revealed that the exponent ‘b’ for Stolephorus tri was very close to the isometric value (b = 3). Therefore, the relative growth of Stolephorus tri was isometric in the coastal waters of Besut, Terengganu.